Ag3V2(PO4)2F3, a new compound obtained by Ag+/Na+ ion exchange into the Na3V2(PO4)2F3 framework. Issue 22 (21st May 2018) - Bianchini, M.; Lalère, F.; Nguyen, H. B. L.; Fauth, F.; David, R.; Suard, E.; Croguennec, L.; Masquelier, C.
Abstract : A new fluorophosphate polyanionic compound has been made by Ag + /Na + ion exchange, leading to several potential technological applications. Abstract : Phosphate polyanionic compounds have been used for several technological applications and are especially widespread in battery research. Na3 V2 (PO4 )2 F3 is a material that holds great promise as a positive electrode for Na-ion batteries. We study here the Ag + /Na + ion exchange that is possible due to the high ionic mobility of Na + in this material. A nearly complete ion exchange was obtained and we report the crystal structure of the new orthorhombic phase Ag3 V2 (PO4 )2 F3, determined by synchrotron X-ray and neutron powder diffraction. Silver occupies the same crystallographic sites as sodium and, except for the differences caused by steric effects, Ag3 V2 (PO4 )2 F3 preserves the symmetry constraints already present in the parent compound Na3 V2 (PO4 )2 F3 . We also followed the evolution of the crystal structure upon heating/cooling, to observe an order/disorder transition analogous to the one already reported for Na3 V2 (PO4 )2 F3, but occurring at a significantly higher temperature.